2022
DOI: 10.1002/jbt.23071
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine, a metabolic modulator, attenuates silica‐induced pulmonary fibrosis and decreases lactate levels and LDH activity in rats

Abstract: Pulmonary fibrosis has been recently linked to metabolic dysregulation. Silicainduced pulmonary fibrosis in rats was employed by the current study to explore the effects of trimetazidine (a metabolic modulator-antianginal drug; TMZ) on silicainduced pulmonary fibrosis. Pulmonary fibrosis was induced by intranasal instillation of silica (50 mg/100 µl/rat) in TMZ versus vehicle-treated rats. Body weights of rats, weights of lungs, and wet-to-dry lung weights were determined. Various parameters were also measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Western blot analysis of lung lysates revealed elevated levels of collagen I and fibronectin in the silicosis group, collectively demonstrating silica-induced pulmonary fibrosis in mice [86]. Similarly, several studies have confirmed that intranasal silica instillation can induce pulmonary fibrosis in both mice and rats [87][88][89].…”
Section: Fig 1 Potential Mechanism Of Ae-pf In Animal Modelsmentioning
confidence: 90%
“…Western blot analysis of lung lysates revealed elevated levels of collagen I and fibronectin in the silicosis group, collectively demonstrating silica-induced pulmonary fibrosis in mice [86]. Similarly, several studies have confirmed that intranasal silica instillation can induce pulmonary fibrosis in both mice and rats [87][88][89].…”
Section: Fig 1 Potential Mechanism Of Ae-pf In Animal Modelsmentioning
confidence: 90%
“…Silica-induced pulmonary fibrosis studies in rats were done to explore the effects of this drug over the LDH activity. The results showed that the derivative of compound 93 was able to reduce and normalize the levels of the enzyme in bronchoalveolar lavage fluid (BALF) [164]. TMZ can be used alone or in combination with antineoplastic drugs, such as gemcitabine or abraxane, to reduce cell viability and induce apoptosis in human pancreatic cancer cells [165].…”
Section: Pyridazine and Piperazinementioning
confidence: 99%